Wigwamma scenozonion sp.nov. (Prymnesiophyceae) from West Greenland - Thomsen, H. A. (British Phycological Journal, 1980)
Wigwamma scenozonion sp. nov. (Prymnesiophyceae) is described on the basis of electron microscopy of shadowcast whole mounts prepared from water samples collected in the vicinity of Godhavn (West Greenland) in July and August 1977. This nanoplanktonic coccolithophorid possesses two smooth flagella and a shorter coiling haptonema. Coccoliths of one type cover the whole cell. Each coccolith is composed of a ring of rod-like crystallites joined end to end and arranged parallel to the edge of the oval coccolith base-plates. A single enlarged crystallite is found on most coccoliths. W. scenozonion is distinguished from the two previously described Wigwamma species by the lack of coccolith superstructures and by having one, rather than two rings of crystallites along the base-plate edge. In addition to the West Greenland specimens a single W. scenozonion cell has been encountered in a water sample from Denmark.